R&R sago krunch, a business plan for small-scale production of ready-to-eat breakfast cereals using sago flour - Balaba, Reneelou Solito (2011)
The R&R Comapany is a company formed out of the general partnership of Reneelou Solito Balaba and Rhezalyn Solito Balaba. The R&R Company will be pioneering in the production and distribution of Sago Krunch in the market. The company envisions in competing and excelling globally and will be setting the trend in terms of utilizing sago flour in breakfast cereals. The identified opportunities such as the existence of financing firms and established laws like BMBE law would greatly aid the R%=&R Company in gaining its advantage in the market. Two set of options in terms of sources of capital were presented and analyzed. The Return on Investment and Net Profit Margin of the two options on financing the company would pave way on making pore practical decision on pursuing the business. Both options presented have a positive result in terms of calculated ROI and NPM, however, for practical reason, it is much better to adopt on acquiring capital from bank loans to fully maximize and utilize the equity by investing the money to other business or savings.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2011
Keywords: R&R Company; Return on Investment (ROI); Net Profit Margin (NPM); Financing firms; Sago krunch; Sago flour; Breakfast cereals; Cereals; Ready-to-eat breakfast cereals; Small-scale production; Sago breakfast cereals